Stevia rebaudiana: Reporting data from the sweetener crop for researchers and smallholder farming assistants - José Walter Pedroza Carneiro; Jasper José Zanco; Antonio Carlos Andrade Gonçalves; Solange Maria Bonaldo; Renan Santos Uhdre (Acta Scientiarum. Agronomy, 2024)
In science, technology and assistance to smallholder farming or large crop acreages of Stevia rebaudiana is necessary to report data using information components to facilitate investors to understand the local field conditions to make assertive economic decisions for long periods. Stevia rebaudiana produces consistent natural sweeteners with safe performance as reported in a multitude of scientific publications. The leaf chemicals components are suitable to humans with healthy disorders affected by the consumption of sugarcane or many other industrial sweeteners. Otherwise, aspects related to the agriculture of sweeteners production still require additional discussion to improve qualitative and quantitative traits necessary for cultivating cost-effective crops. The current text highlighted some agriculture decisions necessary to make the crop more profitable to investors as researchers, agriculture influencers, farmer assistants and consultants of companies looking for alternatives within agro-ecological systems.